Essential Role of the cVRG in the Generation of Both the Expiratory and Inspiratory Components of the Cough Reflex - Cinelli, E; Iovino, L; Bongianni, F; Pantaleo, T; Mutolo, D (Physiological research, 2020)
As stated by Korpáš and Tomori (1979), cough is the most important airway protective reflex which provides airway defensive responses to nociceptive stimuli. They recognized that active expiratory efforts, due to the activation of caudal ventral respiratory group (cVRG) expiratory premotoneurons, are the prominent component of coughs. Here, we discuss data suggesting that neurons located in the cVRG have an essential role in the generation of both the inspiratory and expiratory components of the cough reflex. Some lines of evidence indicate that cVRG expiratory neurons, when strongly activated, may subserve the alternation of inspiratory and expiratory cough bursts, possibly owing to the presence of axon collaterals. Of note, experimental findings such as blockade or impairment of glutamatergic transmission to the cVRG neurons lead to the view that neurons located in the cVRG are crucial for the production of the complete cough motor pattern. The involvement of bulbospinal expiratory neurons seems unlikely since their activation affects differentially expiratory and inspiratory muscles, while their blockade does not affect baseline inspiratory activity. Thus, other types of cVRG neurons with their medullary projections should have a role and possibly contribute to the fine tuning of the intensity of inspiratory and expiratory efforts.
Keywords: Exhalation; Humans; mikroinjekce; zvířata; nadechnutí; kašel; Inhalation; nervus phrenicus; antagonisté excitačních aminokyselin; Microinjections; Reflex; Neurons; medulla oblongata; Phrenic Nerve; Respiratory Mechanics; Cough; Excitatory Amino Acid Antagonists; vydechnutí; reflex; Animals; lidé; Medulla Oblongata; 6-kyano-7-nitrochinoxalin-2,3-dion; neurony; mechanika dýchání; 6-Cyano-7-nitroquinoxaline-2,3-dione